Quantitative dobutamine stress echocardiography for the early detection of cardiac allograft vasculopathy in heart transplant recipients. Issue 2 (4th October 2007) - Eroglu, E; D'hooge, J; Sutherland, G R; Marciniak, A; Thijs, D; Droogne, W; Herbots, L; Van Cleemput, J; Claus, P; Bijnens, B; Vanhaecke, J; Rademakers, F
Abstract : Background: A non-invasive method to detect the presence of cardiac allograft vasculopathy (CAV) remains an important goal in clinical cardiology. Objective: To assess the value of quantitative dobutamine stress echocardiography (DSE) for the early detection of CAV. Methods: 42 heart transplant recipients underwent DSE with acquisition of both conventional two-dimensional and colour tissue Doppler data. All studies were analysed conventionally and quantitatively using regional deformation parameters—that is, peak systolic longitudinal strain (∊peak sys ), strain rate (SRpeak sys ) and post-systolic strain index. Myocardial segments were classified as normal, mildly abnormal or severely abnormal based on correlative angiographic findings. Results: At baseline, ∊peak sys was significantly lower in severely abnormal segments than in normal ones. However, at peak stress, ∊peak sys was able to separate three groups of segments. Receiver operating characteristic analysis showed an SRpeak sys response of <0.5/s to identify patients with CAV with a sensitivity of 88%, specificity of 85% and a negative predictive value of 92%. Conclusion: Regional myocardial function is impaired in heart transplant recipients with CAV even when the disease is considered to be non-significant on conventional angiography. Systolic deformation parameters tended to detect the existence of CAV more accurately than conventional visual DSE assessment. Strain rate imaging during stress can therefore safely be used as a non-invasive screening test for detecting CAV in heart transplant recipients.